LEGAL PROTECTION OF LAND FROM POLLUTION - Petrović, Zdravko; Manojlović, Dragan; Jović, Vojislav (Economics of Agriculture, 2014)
Situated in the study conducted in this paper, using the method of analysis of contents, induction and deduction, historical and legal dogmatic indicated that ecology as their object of legal protection has three global natural values: air, water, land, and atmosphere, hydrosphere and lithosphere as constituent elements of the biosphere. Land as a special natural product comprises a solid layer of the Earth that is specifc to the biosphere. The importance of land from the perspective of sustainable development is multifaceted, especially when seen through its environmental, industrial, manufacturing, socio-economic, educational, scientifc, cultural, historical and any other useful functions. Its most important function is to fertility and the ability to flora supplying water, oxygen and mineral substances. Natural processes that led to the creation of land argue the view that it belongs to the so-called renewable resources, but only if its a man rational use and encourages their natural reproduction. In accordance with current legislation and categorization of land, this survey includes agricultural land. In this paper, we have opted for ecological and legal land protection as one of the most important natural resources whose quality and extent of a very signifcant impact on the environment as a whole. The introductory part of the paper included a terminological demarcation and specificity of the case study of environmental law, as well as the possible forms of soil pollution. Methodological framework of research, using the method of content analysis of existing domestic and international legal legislation, method comparison and synthesis were studied legal documents that protect the land from pollution.